The Shared and Distinct Mechanisms Underlying Fear of Evaluation in Social Anxiety: The Roles of Negative and Positive Evaluation - Gao, Wei; Li, Yanping; Yuan, JiaJin; He, Qinghua (Depression and anxiety, 2025)
Social anxiety disorder (SAD) is associated with persistent fear of negative evaluation (FNE) and fear of positive evaluation (FPE), which play critical roles in the development and maintenance of anxiety symptoms. However, it remains unclear how FNE and FPE contribute to the common and different symptoms of social anxiety. In this review, we tried to elucidate the shared and distinct mechanisms underlying fear of evaluation and clarify the impact of FNE and FPE on social anxiety by integrating the theories, external expressions, and internal mechanisms. First, FNE and FPE share evolutionary functions but have distinct motivations for maintaining social role stability. Second, FNE and FPE share similar emotions and avoidance behaviors but contribute to distinct comorbid symptoms in SAD, including eating disorders and alcohol abuse. Third, FNE and FPE share emotional and social pain circuits but have different dysfunctions in the prefrontal, cingulate, and reward brain regions, which are associated with rejection sensitivity and anhedonia features. Overall, this review sheds light on the cognitive and neural mechanisms of SAD based on fear of evaluation, highlighting both the shared and distinctive aspects of FNE and FPE. These insights have important implications for the development of effective interventions for social anxiety.